Public-private partnership and schooling outcomes across countries - Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2006)
The paper provides a comparative analysis of the association between student achievement and public-private partnerships (PPPs) in schooling across countries. Student-level data from the PISA international achievement test provides information on the public-private character of both operation and funding of each tested school. Across countries, public operation is associated with lower student outcomes, but public funding with better student outcomes. Thus, systems of PPPs that combine private operation with public funding do best among all possible operation-funding combinations, while PPPs that combine public operation with private funding do worst. The advantage of private operation is particularly strong in countries with large shares of public funding.
Keywords: I20; H52; H42; L33; 330; Bildungsniveau; Schule; Privatschule; Public-Private Partnership; Schätzung; Welt